Review on pelletization techniques - Prashanthi.P; Pavani.A; Bhagavan Raju. M (International Journal of Pharmacy and Analytical Research, 2022)
Pellets are multiparticulate dosage form consisting of a multiplicity of small discrete units each exhibit some desired characteristics. Pellets are small free flowing, Spherical or semi spherical units with size and diameter ranging from 0.5-1.5mm. The present review deals with the outline of the pellets, pellets growth mechanism and various types of pelletization techniques like extrusion/spheronization, layering, Cryopelletization, freeze pelletization, spray congealing, spray drying. Among various techniques now-a-days fluid bed processor is most widely used in the pharmaceutical industry due to its uniform coating and highly efficiency. Fluid bed processor involves different spray process i.e top spray, bottom spray and tangential spray. Fluid bed processor has wide range of applications such as drying, particle coating and pelletizing.